Characteristics of aerosol optical depth retrieved from AERONET in Vietnam and comparison with MODIS data - Thanh, Pham Xuan; Anh, Nguyen Xuan; Khuong, Pham Le; Thuy, Do Ngoc; Son, Hoang Hai; Son, Nguyen Xuan; Tuan, Au Duy (Vietnam Journal of Earth Sciences, 2016)
In this paper, we summarized aerosol optical depth (AOD) data retrieved from AERONET (Aerosol RObotic NETwork) sites in Vietnam. The characteristics of AOD (Aerosol Optical Depth) retrieved from AERONET has been validated and compared with AOD retrieved from MODIS/Terra satellite. Firstly, AOD at 500nm retrieved from AERONET sites are used to evaluate the mean value, annual variation, diurnal variation and variable trend of AOD. Then, the interpolation techniques have been used to derive AOD at 550nm from AOD at 500nm and compare with AOD retrieved by MODIS satellite data. The monthly averaged error, annual averaged error, root mean square error and correlation coefficient are used to compare. As a result, the averaged AOD value is 0.68; 0.70; 0.25 and 0.24 in Bac Giang, Nghia Do, Nha Trang and Bac Lieu, respectively. The annual variation of Bac Giang, Nghia Do and Nha Trang has two peaks (in October and March) and two minimum values (in December, June and July). At Bac Lieu site, there is a maximum value in Jannuary and a minimum ones in July. At all sites, most of the anomalies were annually observed in the period of AOD maximum. In the monitoring period, AOD trend slightly decreased in Bac Giang and significantly decreased in Nghia Do . The annual average differences are 0.09, 0.13, 0.05 and 0.11 in Bac Giang, Nghia Do, Nha Trang and Bac Lieu, respectively. The root mean square errors (RMSEs) are 0.23, 0.22, 0.09, and 0.16 for Bac Giang, Nghia Do, Nha Trang and Bac Lieu, respectively. The correlation between MODIS AOD and AERONET AOD is found to be quite high (r=0.90) at Nghia Do. For other sites, the correlation coefficients are 0.87, 0.85, 0.79 at Bac Giang, Nha Trang and Bac Lieu, respectively. References Nguyễn Xuân Anh, Lê Việt Huy, 2008: Nghiên cứu aerosol qua trạm Bắc Giang và Bạc Liêu. Tuyển tập các công trình nghiên cứu vật lý địa cầu 2008, trang 307-320. Holben B. N., T. F. Eck, I. Slutsker, T. Tanre, J. P. Buis, A.Setzer, E. Vermote, J.A. Reagan, Y. J. Kaufman, T.Nakajima, F. Lavenu, I. Jankowiak, and A. Smirnov, 1998: AERONET: a federated instrument network and data archive for aerosol characterization. Remote Sens. Environ., 37 : 2403 - 2412. Kaufman Y. J., Didier Tanre, and Olivier Boucher, 2002: A satellite view of aerosols in the climate system. Nature, 419: 215-223, 2002. 29 Nguyễn Trọng Hiệu, Phạm Thanh Hương, Lê Thị Bảo Ngọc, 2005: Một số dị thường khí hậu tiêu biểu ở Việt Nam thời kỳ 1961-2000. Tạp chí Khí tượng Thủy văn, tr.1-9. Lau K.-M. et al., 2008: The joint Aerosol-Monsoon Experiment: A New Challenge for Monsoon Climate Research. Bulletin of the American Meteorological Society, Vol 89, 369-383. Mielonen T. , R. C. Levy, V. Aaltonen, M. Komppula, G. de Leeuw, J. Huttunen, H. Lihavainen, P. Kolmonen, K. E. J. Lehtinen, and A. Arola1, 2011: Evaluating the assumptions of surface reflectance and aerosol type selection within the MODIS aerosol retrieval over land: the problem of dust type selection Atmos. Meas. Tech., 4, 201-214. Sanjay More, P. Pradeep Kumar, Pawan Gupta, P.C.S. Devara, G.R. Aher, 2013: Comparison of Aerosol Products Retrieved from AERONET, MICROTOPS and MODIS over a Tropical Urban City, Pune, India. Aerosol and Air Quality Research, 13: 107-121. Phan Văn Tân, 2005 : Phương pháp thống kê trong khí hậu. Nhà xuất bản Đại học Quốc gia Hà Nội, 260 trang. Phạm Xuân Thành, Nguyễn Xuân Anh, Lê Việt Huy, Lê Như Quân, Hoàng Hải Sơn, Phạm Lê Khương, 2011: Ảnh hưởng của mưa đầu mùa tới độ dày quang học sol khí tại Bạc Liêu. Tạp chí Các Khoa học về Trái Đất, T.33, (1), tr.10-17. Phạm Xuân Thành, Nguyễn Xuân Anh, Đỗ Ngọc Thuý, Lê Việt Huy, 2012: Ảnh hưởng của hoàn lưu gió mùa mùa đông tới độ dày quang học sol khí tại Bạc Liêu và Bắc Giang. Tạp chí Các khoa học về Trái Đất, 34, (3), tr.266-274 Phạm Xuân Thành, Nguyễn Xuân Anh, Đỗ Ngọc Thúy, Phạm Lê Khương, Hoàng Hải Sơn, Nguyễn Ngọc Quang, 2014: So sánh độ dày quang học sol khí từ nguồn số liệu MODIS và AERONET tại khu vực Bắc Giang. Hội thảo khoa học “Công nghệ vũ trụ và ứng dụng”, Hà Nội. Tripathi S. N., Sagnik Dey, A. Chandel, S. Srivastava, Ramesh P. Singh, B. N. Holben, 2005: Comparison of MODIS and AERONET derived aerosol optical depth over the Ganga Basin, India. Annales Geophysicae, 23, 1093-1101. Qifang Xu, Zoran Obradovic, Bo Han, Yong Li, Amy Braverman, Slobodan Vucetic, 2005: Improving Aerosol Retrieval Accuracy by Integrating AERONET, MISR and MODIS Data. 8th International Conference on Information Fusion, 25-28 July 2005. Qi YuLei, GE JinMing & Huang JianPing, 2013 : Spatial and temporal distribution of MODIS and MISR aerosol optical depth over northern China and comparison with AERONET. Chinese Science Bulletin, Vol.58 No.20: 249-2506,doi: 10.1007/s11434-013-5678-5. http://modis.gsfc.nasa.gov/